Increasing the Degree of Crushing of the Soil When Processing Between the Row of Categories - Saidrakhim Umarovich Temirov; Askarjonov Shohijakhan (American Journal of Botany and Bioengineering, 2025)
In the article, the conclusion is made that at between line the processing cotton group of a degree chopping up of ground can ensure at the expense of level-by-level processing or beforehand, that is before pass of working bodies cultivator of cutting of its surface in cross and longitudinal directions with the help special are narrow a knife.